Rupture of a Type B Aortic Dissection in a Postpartum Patient with Marfan Syndrome - Patberg, Elizabeth; Duffy, Jennifer; Hameed, Afshan B. (American Journal of Perinatology Reports, 2019)
Background Pregnant women with Marfan syndrome (MFS) are known to be at increased risk of aortic dissection; however, cases of aortic rupture are extremely rare. There is lack of consensus on the exact site and size of aortic diameter measurement that increases this risk, and whether this applies to both Type A and Type B dissections.Case A 23-year-old G2P1001 with known Marfan syndrome who underwent an uncomplicated antepartum and intrapartum course. She experienced persistent backache 10 days postpartum that led to the diagnosis of Stanford Type B dissection. The patient was hospitalized for close observation. Dissection progressed to aortic rupture within 24 hours that required emergent thoracic endovascular aortic repair. She had an uncomplicated postoperative course.Conclusion Our report demonstrates rupture of a known aortic dissection within a very short time in the postpartum period. The case highlights the importance of patient education and close surveillance especially in the postpartum period. It also brings home the value of imaging of the whole aorta rather than focusing on the ascending alone. Multidisciplinary care and timely diagnosis and intervention likely led to the favorable outcome in our case.
Keywords: Marfan syndrome; pregnancy; aortic rupture; Type B aortic dissection